Development of a local bacterial isolate expressing cyclodextrin glycosyltransferase through molecular cloning approaches - Ramli, Norhayati (2012)
Cyclodextrin glycosyltransferase (CGTase, EC 2.4.1.19) exhibited as an important member of the amylolytic glucosylase family that catalyzed the formation of cyclodextrins (CDs) through cyclization reaction. The ability of CGTase to convert starch into CD brings a great interest to the researchers. The formation of CDinclusion complex with variety of guest molecules was advantageous as the enhancement of the physical and chemical properties of the inclusion complex formed were beneficial in biotechnology, pharmaceutical, food, cosmetic, chemical and agricultural field. However, the obstacle in producing the CD in industrial scale was due to the production of different ratios of α-, β- and γ-CD catalyzed by CGTases. The above phenomenon contributed to the complicated and tedious purification strategy of the final targeted product. Due to the high viscosity of starches, pre-treatment stage was needed in order to prevent the blockage in the membrane system in filtration stage. Furthermore, the low concentration of CGTase produced by wild type strain at longer incubation time caused the major problem for CGTase production in large scale. Hence, the objectives of this study were to isolate and screen the potential CGTase producer. The isolated strain was then subjected to the isolation of CGTase gene using primer screening technique and used for construction of CGTase expression system in Escherichia coli. The enzyme produced from recombinant strains was evaluated. In this study, the CGTase-producing bacteria were successfully isolated from the soil in Malaysia. Out of 65 strains, eleven CGTase producers has been further screened using modified Horikoshi agar type II with specific indicator. The size of halo zones formation on the plate indicates a good qualitative measurement of CGTase producer as the biggest diameter formed is indicating the highest CGTase activity obtained.All eleven isolates showed the characteristics of Gram positive and identified as Bacillus sp. Furthermore, the selection for the best CGTase producer was carried put with the highest CGTase activity (11.709 U/mL) and CD concentration (0.011, 2.504 and 0.188 mg/mL for α-, β- and γ-CD, respectively) were produced by Bacillus sp. NR5 UPM using raw soluble starch as a substrate at 48 hours of fermentation. This isolate also showed the highest CGTase activity (15.514 U/mL) at 32 hours of fermentation with the used of sago starch as a substrate. The isolate Bacillus sp. NR5 UPM has the capability in predominantly producing β-CD as a main product and hasa potential in degrading the raw tarch, thus known as a raw-starch degrading enzyme producer. Further study on the isolation of CGTase gene from Bacillus sp. NR5 UPM DNA was successfully carried out using DNA walking strategy. Analysis of the nucleotide sequences revealed the presence of an open reading frame of 2112 bp which encoded a protein containing 704 amino acids with a putative molecular weight of 78.6 kDa. The deduced amino acids sequence showed about 98% homology with the CGTase from Bacillus sp. KC201. The recognition of TTG as a start codon was assisted by the presence of Shine-Dalgarno sequence, which located at 6 bp upstream from the initiation codon. Meanwhile, the presence of 29 amino acids residues of the isolated CGTase was functioned as signal peptide which facilitated in the secretion of protein. The pUC19CGT-SS expression system has been constructed by cloning the full length of CGTase gene under the transcriptional control of lac promoter of pUC19 into an E. coli. Compared to wild type, the CGTase that was produced in recombinant strain only required one-fourth of culture time and neutral pH to produce CGTase. After 12 hours of cultivation, the CGTase activity in the culture medium reached 29.6 U/mL, which was approximately 2.5-fold higher than the CGTase produced by the parental strain. Interestingly, 94% of the CGTase activity was detected in an extracellular space, indicating the signal peptide was functional in E. coli. In addition, the isolation of the promoter and transcriptional terminator of CGTase from Bacillus sp. NR5 UPM was carried out. The functionality of an insertion of putative promoter regions upstream of CGTase gene was verified by the construction of E. coli strain harbouring pTZCGT-BS, which showed approximately 3.2-fold increment of CGTase a support the important function of the strong promoter in regulating the expression level of enzyme. In conclusion, the study on the strain development from Bacillus sp. NR5 UPM by expressing CGTase gene into E. coli expression system was successfully carried out with the improved enzyme activity from the recombinant strain.